Manfaat Pemeliharaan Apotek Hidup Di Lingkungan Posyandu Kelurahan Tuah Karya Dalam Menjaga Daya Tahan Tubuh Di Masa Pandemi Covid – 19 - Fezi Waldeseska Aulia; Agustry Akbarsyah; Anggita Aditia Hutabarat; Mentari Dwi Aristi (Jurnal Pengabdian UntukMu NegeRI, 2022)
The Tuah Karya community in utilizing the Posyandu yard land has not been used optimally, this needs to be done by managing the yard for the maintenance of live pharmacy plants in addition to decorating the posyandu environment as well as medicine, especially during the COVID-19 pandemic, it is required to maintain endurance. Live apothecary plants have very good content to maintain the immune system. KKN Students Together Against COVID19 conducted socialization and training to the Tuah Karya sub-district community regarding the maintenance of live pharmacy plants in maintaining body resistance. The results of these activities are expected that the community is aware, interested, and interested in growing live pharmacy plants in their own yard, then able to increase knowledge about the use of posyandu yard land for planting live pharmacy plants, and the public can know plants that can be used for medicine as living pharmacies.